Measurement of School Effectiveness Using Iso 21001:2018 - Management Systems for Educational Organizations (EOMS) - Ugwulashi, Chima Sebastine; MBA, Callistus Okechukwu (International Journal of Educational Management, 2021)
Education has been a major instrument for individuals and national transformation. Education develops manpower needs, thus, educational institutions have to operate efficiently and effectively in safe manner to meet the changing scientific and technological perspectives making the world a global unit. The school is a formal system standardized for teaching and learning to meet national and global goals. School measurement process is an important aspect in determining the inefficacies or efficacies of the system performances in meeting global market needs. The International Standard Organization provided ISO 21001:2018 known as Management Systems for Educational Organizations (EOMS), to manage education for quality results. The standard has ten principles which appeared like a checklist for measurement of school effectiveness. This paper advocates for the use of ISO 21001:2018 principles in measurement of school effectiveness as good stance in achieving quality innovations at various educational levels in Nigeria. Therefore, it is recommended that the principles of ISO 21001:2018 be the benchmark for measurement of school effectiveness. It should be applied as standard procedures for establishment of school. Finally, as a check for proprietors, government and other interested parties to adequately provide quantitative and qualitative staffing, infrastructures and other resources focused on development of the learners amongst others.